Analysis of Student Learning Interests Based on Peer Learning Interests According to Crowds Behavior Theory - Luthfia, Izza; Basori, Basori; Kurniasari, Kurniasari (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2024)
The findings of observations collected at school showed that students in class XI PPLG B still had relatively low levels of learning interest and that those students' interests were heavily influenced by those of their peers, which served as the basis for this study. This study used the Crowd Behavior Theory to analyze students' learning interests about the interests of their peers. Descriptive-analytical study using a qualitative approach was the methodology employed. Thirty-five students from class XI PPLG B and one teacher in the PPLG area of competence participated in the study. Purposive sampling was the method used to choose the participants. Data for the study were gathered through interviews and observation. While the interview instrument employed multiple question items that were submitted to the informant, the class teacher, the observation instrument used an observation sheet with several statement items. The data analysis results indicate that students' learning interests are significantly influenced by their peers' learning interests. According to the teacher's interview, groups with similar goals and perspectives might arise from the interactions of peers with different behavioral tendencies. The influence of peers has a direct effect on other students' learning spirits, as evidenced by the observational data. The idea that an individual's interest in learning may be influenced by their group is supported by Le Bon's (2002) Crowd Behavior Theory, which is consistent with this.